Factors informing training load during the transition from club to national football teams - Gould, J. J.; Clements, E.; Ehrmann, F.; Duffield, R. (International Journal of Sports Physiology and Performance, 2024)
Purpose: This study examined the relationship of precamp match exposure, travel demands, perceptual wellness, and musculoskeletal screening with ensuing training load (TL) during national-team (NT) duties for international footballers (soccer).